Population based cohort study of fetal deaths, and neonatal and perinatal mortality at term within a Somali diaspora - Stephen Contag; Rahel Nardos; Irina A. Buhimschi; Jennifer Almanza (BMC, 2021)
Abstract Background Somali women deliver at greater gestational age with limited information on the associated perinatal mortality. Our objective is to compare perinatal mortality among Somali women with the population rates. Methods This is a retrospective cohort study from all births that occurred in Minnesota between 2011 and 2017. Information was obtained from certificates of birth, and neonatal and fetal death. Data was abstracted from 470,550 non-anomalous births ≥37 and ≤ 42 weeks of gestation. The study population included U.S. born White, U.S. born Black, women born in Somalia or self-identified as Somali, and women who identified as Hispanic regardless of place of birth (377,426). We excluded births < 37 weeks and > 42 weeks, > 1 fetus, age < 18 or > 45 years, or women of other ethnicities. The exposure was documented ethnicity or place of birth, and the outcomes were live birth, fetal death, neonatal death prior to 28 days, and perinatal mortality rates. These were calculated using binomial proportions with 95% confidence intervals and compared using odds ratios adjusted (aOR) for diabetes, hypertension and maternal body mass index. Results The aOR [95%CI] for stillbirth rate in the Somali cohort was greater than for U.S. born White (2.05 [1.49-2.83]) and Hispanic women (1.90 [1.30-2.79]), but similar to U.S. born Black women (0.88 [0.57-1.34]). Neonatal death rates were greater than for U.S. born White (1.84 [1.36-2.48], U.S. born Black women (1.47 [1.04-2.06]) and Hispanic women (1.47 [1.05-2.06]). This did not change after analysis was restricted to those with spontaneous onset of labor. When analyzed by week, at 42 weeks Somali aOR for neonatal death was the same as for U.S. born White women, but compared against U.S. born Black and Hispanic women, was significantly lower. Conclusions The later mean gestational age at delivery among women of Somali ethnicity is associated with greater overall risk for stillbirth and neonatal death rates at term, except compared against U.S. born Black women with whom stillbirth rates were not different. At 42 weeks, Somali neonatal mortality decreased and was comparable to that of the U.S. born White population and was lower than that of the other minorities.